EFFECT OF TRAINING AND LEADERSHIP SKILLS ON EMPLOYEE PERFORMANCE IN DEVOLVED GOVERNMENTS IN KENYA: A CASE OF WAJIR COUNTY - Jehow, Fatuma Abdi; Gikandi, Dr. Joyce; Mwencha, Dr. Peter (European Journal of Business and Strategic Management, 2018)
Purpose: The main purpose of this study was to effect training and leadership skills on employee's performance in Wajir County, Kenya. Methodology: The study employed descriptive survey design and the target population of the study was 153 senior, middle and lower level managers at Wajir county Government. The stratified random sampling method was used in selecting the respondents in all the thirteen departments. The sample size was 111. The study used questionnaires to collect the required data. Descriptive statistics was used mainly to summarize the data. SPSS was used for analysing complex data. Data presentation was through the use of pie charts, bar charts, graphs and frequency tables. Regression and Correlation analysis was used to establish the relationship between the independent and dependent variables. Results: The study found out that training and development improved employees' skills and knowledge leading to better performance; it created job satisfaction and the county would be able to retain the qualified employees it employed and it improved performance thus achievement of targets. Training and development also boosted employee career growth. The study also found out those supervisory skills of managers/supervisors affected employee motivation at Wajir County positively Policy recommendation: County Government of Wajir should create and execute clear workers training and advancement programs that are worker headed to permit staff procure the essential aptitudes and map out their vocation improvement plan which thus positively affects worker performance. Keywords: Training, leadership skills, and employee performance